Высокоточный трехканальный дифференциальный электропривод с подчиненным регулированием для механизма подачи обрабатывающего центра - Худяев, Александр Андреевич; Пшеничников, Дмитрий Алексеевич; Поленок, Виталий Викторович (НТУ "ХПИ", 2013)
The kinematic charts and mathematical model of mechanical part, and structural diagram of control system of the iterative type threechannel differential servodrive of machining center feeding mechanism are considered. The results of computer simulation of dynamic and accuracy characteristics for estimation of efficiency proposed three-channel servosystem are given.
Keywords: следящие системы САУ; инерционные рабочие органы; итерационный трехканальный электропривод; обрабатывающий центр повышенной точности; компьютерное моделирование характеристик